2019
DOI: 10.3847/2041-8213/ab2c00
|View full text |Cite
|
Sign up to set email alerts
|

CHIME/FRB Detection of the Original Repeating Fast Radio Burst Source FRB 121102

Abstract: We report the detection of a single burst from the first-discovered repeating Fast Radio Burst source, FRB 121102, with CHIME/FRB, which operates in the frequency band 400-800 MHz. The detected burst occurred on 2018 November 19 and its emission extends down to at least 600 MHz, the lowest frequency detection of this source yet. The burst, detected with a significance of 23.7σ, has fluence 12±3 Jy ms and shows complex time and frequency morphology. The 34 ms width of the burst is the largest seen for this arXi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

18
118
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 143 publications
(136 citation statements)
references
References 32 publications
18
118
0
Order By: Relevance
“…Ultra-wideband or simultaneous multi-band observations will also allow tests of this scintillation model, by characterizing the frequency dependence of the decoherence bandwidth, which we predict to scale as Δν d ∝ν α with α≈4, as discussed above. Similar studies of the original repeating FRB source, FRB 121102, have characterized the observed drift of components to lower frequencies at later times (e.g., Hessels et al 2019;Josephy et al 2019). Caleb et al (2020) fit the drift rate as a function of frequency using a linear model, n µ…”
Section: Discussionmentioning
confidence: 92%
“…Ultra-wideband or simultaneous multi-band observations will also allow tests of this scintillation model, by characterizing the frequency dependence of the decoherence bandwidth, which we predict to scale as Δν d ∝ν α with α≈4, as discussed above. Similar studies of the original repeating FRB source, FRB 121102, have characterized the observed drift of components to lower frequencies at later times (e.g., Hessels et al 2019;Josephy et al 2019). Caleb et al (2020) fit the drift rate as a function of frequency using a linear model, n µ…”
Section: Discussionmentioning
confidence: 92%
“…To date, FRB121102 has been detected at radio frequencies from 600 MHz (Josephy et al 2019) up to 8 GHz (Gajjar et al 2018). Early observations of FRB121102 by Spitler et al (2016) and Scholz et al (2016) demonstrated that the bursts have variable spectra that sometimes peak within the observing band and are often not well modeled by a power law.…”
Section: Discussionmentioning
confidence: 99%
“…Gajjar et al 2018). More recently, a single burst from this FRB was reported in the upper half of the CHIME 400 -800 MHz band (Josephy et al 2019).…”
mentioning
confidence: 83%